(untitled) (Geo-Eco-Marina, 2019)
This paper presents investigation carried out on two sections containing successions of the middle Sarmatian s.l. (Bessarabian) and upper Sarmatian s.l. (Khersonian). Both substages are mainly characterized, from lithological point of view, by the presence of chalky limestones, argillaceous limestones, oolithic limestones and coquinas. The boundary between the two substages is marked by coquinas mainly containing small-sized specimens of the bivalve Cardium spp. The upper Bessarabian is characterized by the Plicatiforma fittoni bivalve zone, while in the Khersonian substage the Mactra caspia bivalve zone, followed by Mactra bulgarica biozones are present. The Techirghiol section contains no calcareous nannofossils, while in the Limanu section a few specimens assigned to the genus Noelaerhabdus were discovered in the upper Bessarabian. This finding indicates a possible connection of the South Dobrogea (part of the Euxinian-Caspian domain) with the Central Paratethys, during the middle Sarmatian s.l. (Bessarabian).